Does 'living by water' still exist? A new perspective for quantifying ISA dynamics at different distances from the Yangtze River - Yaqing Bai; Yugang Tian; Bo Geng; Xinbo Liu; Kun Zheng (Ecological Indicators, 2024)
Since ancient times, human beings have had the universal law of “living by water”, and the Yangtze River plays a crucial role in promoting socioeconomic development. Impervious surface area (ISA) is the key indicator of urban expansion and can effectively reflect human activities. Therefore, based on long time-series data of ISA, we used the combination of remote sensing, geographical information systems, and spatial statistics to quantify the ISA spatiotemporal evolution patterns at different distances from different sections of the Yangtze River from 1990 to 2020 and proposed the ISA layered development model along riverbanks. The results indicate that the expansion rate of most cities along the Yangtze River had variations and different temporal characteristics among cities of different levels. From the perspective along the Yangtze River, there are certain regularities in the ISA growth. Human dependence on rivers has been decreasing over time, but the closer to the river, the greater the ISA expansion intensity (EI). The fluctuation trends of expansion intensity within different distance ranges (10–50 km) are similar in different sections over time and approximate to “a short head S-shaped curve”, but the size of EI varies in different sections along the Yangtze River. Different sections along the Yangtze River show the pattern of “slow-fast-deceleration, with the highest intensity occurring around 2015”. In the process of urbanization, areas far away from rivers will eventually connect with areas close to rivers, and the regional spatial pattern differences will gradually weaken. Multiple regression analysis indicated that the economic, social, and geographical factors were strongly associated with spatiotemporal differences in ISA expansion. This study will deepen our understanding of human activity changes along the Yangtze River, which is of great significance for implementing the national major strategy of “to step up conservation of the Yangtze River and stop its over development” and achieving the sustainable development between humans and water.